Safeguarding Human Health against Plastics and Petrochemicals: A Scientific and Moral Imperative - Sarah Dunlop; Yannick Mulders; Louise Goodes; Hervé Raps; Philip J. Landrigan (Journal of Moral Theology)
Plastics are a great and growing threat to health. They are associated with stillbirths, premature births, cognitive loss, and cancers in children, as well as with five million cases of heart disease, 350,000 strokes, and 595,000 premature deaths annually in adults. Plastic manufacture releases over two billion tons of CO2 annually, thus accelerating climate change. Plastics’ harms fall disproportionately on low- and middle-income countries and on vulnerable populations in all countries. They result in annual health-related economic losses exceeding $1.5 trillion. An estimated six billion tons of plastic waste pollute the planet; single-use packaging is the main source. When burned, plastic waste releases particulate and toxic pollutants. Reckless increases in production are the main driver of plastics’ worsening harms, and output is projected to treble by 2060. Recycling is not a solution; less than ten percent of plastic can be recycled or reused due to its chemical complexity and toxic content. To address the plastics crisis, UN Member States resolved in 2022 to develop a global plastics treaty. An ethically-grounded treaty will prioritize protection of human health and human rights. Provisions needed to achieve these goals are a global cap on plastic production and strict regulation of plastic chemicals.